The Impact of COVID-19 on the Orthopaedic Surgery Residency Match - Whisonant, Cees T.; Shahriari, Shawhin R. K.; McDonald, Casey; Hough, Tyler; Ederle, Amanda C.; Borah, Gregory L. (The Surgery Journal, 2022)
Introduction Matching into an orthopaedic surgery residency program presents a challenging accomplishment for applicants to achieve in any given year. Due to the profound changes to the application process caused by the coronavirus disease 2019 (COVID-19) pandemic it was theorized that there would be a change in the number of graduates matching close to their home medical school region, state, and program.Methods Orthopaedic surgery residency program Web sites and social media accounts were accessed to elucidate current resident data, including graduates' medical school, and geographical location of their school. Chi-square analysis was performed to identify trends in current residents matching within their home program, state, and region associated with the 2021 orthopaedic match. These numbers were compared with previous year's successful applicants.Results In 2021, a significant 4.4% (p=0.02) increase in successful matches within applicants' home states occurred (33.4% vs. 37.8%) and home programs (p<0.001) when compared with previous years (21.2% vs. 27.4%). However, in 2021, there was no significant change in home region matching (p=0.56) with 60% of successful matches occurring in home regions. This was statistically consistent with what was observed in previous years (61.4%).Conclusion The COVID-19 pandemic was associated with restrictions in travel and interview options resulting in a significant increase in the number of orthopaedic applicants who matched into their home program, or at programs in their home state compared with previous years. Although no statistically significant regional change occurred during the 2021 match, it remains the leading predictor of where successful applicants will match. With many unknowns related to the upcoming match cycles it is important for applicants and programs to have a general idea of recent trends and outcomes to best focus their efforts, especially if diversity and minority inclusion are considered in highly competitive specialties like orthopaedic surgery.
Keywords: orthopaedic surgery; residency; the match; COVID-19 pandemic; graduate medical education